Role of age of incidence, parity, body mass index and socioeconomic class in endometrial carcinoma - Nimbark, Neha A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Endometrial carcinoma is the most common gynecologial malignancy in world. The main aim is to study epidemiological factors of Ca body uterus in our hospital. The present study was designed to evaluate the age of incidence of carcinoma body uterus and study role of parity, body mass index and socioeconomic class in carcinoma body. Methods: This is a prospective study of 50 cases of endometrial carcinoma who were treated in a single unit of the hospital from April 2010 to March 2012 (2 years) conducted at the department of gynaecological oncology G. C. R. I., Ahmedabad. Observational study was done. All these data were combined and tabulated in frequency table simple percentage analysis is used for frequency and percentage analysis is applied to create a contingency table from the frequency distribution and represent the collected data for better understanding. Descriptive statistics were obtained for all variable. Results: Maximum number of patients were in age group of 50-59 years. Mean age was 58 years. Maximum patients were multiparous (54%). 4 patients were nulligravida (9%). 70% were overweight and obese. Majority of patients (72%) belong to middle and higher socio-economic class. Conclusions: It was noted that the incidence for ca endometrium is related to age, parity, BMI and socioeconomic class at our centre.